2016
DOI: 10.1177/1934578x1601101107
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effects of Compounds from Polygonum odoratum

Abstract: Polygonum odoratum is an edible plant traditionally used as an antidiabetic, antimicrobial, anti-inflammatory, and antitumor agent in Asia. The aim of the study was to evaluate the anti-inflammatory effect of P. odoratum and the isolation and characterization of its main fractions. Extracts of the aerial parts were tested for anti-inflammatory activity as indicated by a change in the cytokine secretion in lipopolysaccharide-stimulated macrophages. After separation of the extract by reversed-phase high-performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Biologically scutellarein 7-glucoside shows anti-inflammatory activity by decreasing the IL-6 and TNF-α production as reported by Okonogi et al. ( 2016 ). Another study reported by Goran et al., shows its certain inhibitory activity against indole-3-acetic acid oxidase there by inhibiting ATP formation inside the plant mitochondria (Stenlid, 1976 ).…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Biologically scutellarein 7-glucoside shows anti-inflammatory activity by decreasing the IL-6 and TNF-α production as reported by Okonogi et al. ( 2016 ). Another study reported by Goran et al., shows its certain inhibitory activity against indole-3-acetic acid oxidase there by inhibiting ATP formation inside the plant mitochondria (Stenlid, 1976 ).…”
Section: Resultsmentioning
confidence: 57%
“…In the free form zinc makes coordination bonds with three residues (HIS 374 , HIS 378 and GLU 402 ) and a water molecule (Towler et al, 2004). The leads are explored under two key categories (a) drug candidates undergoing clinical evaluation and (b) natural products (Arts et al, 2004;McGhie & Walton, 2007;Okonogi et al, 2016;Paul et al, 2018;Stenlid, 1976;Yuldashev, 2002) (Table 1). Glide (Friesner et al, 2004) Extra Precision (XP) approach was used for screening of candidates followed by calculation of MM-GBSA energies to increase accuracy, and reliability of the docking process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-inflammatory activity of P. odorata aerial extracts was discovered by Onkologi et al [44] in 2016. This analysis used three different solvents for extraction: water, 50% ethanol in water and ethanol.…”
Section: Anti-inflammatory Effectsmentioning
confidence: 96%
“…P. odorata is also being taken by the Chinese Buddhist to reduce sexual desire [13]. Other than that, P. odorata has many pharmacological effects such as anticancer, antibacterial, anti-inflammatory, anti-fungal and antioxidant [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%